2021
DOI: 10.5371/hp.2021.33.4.231
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Alcohol Use Disorder with Perioperative Complications following Primary Total Hip Arthroplasty

Abstract: Purpose Alcohol use disorder is a leading mental health disorder in the United States. Few studies evaluating the association of alcohol use disorder following primary total hip arthroplasty (THA) have been reported. Therefore, the purpose of this study was to determine whether patients with alcohol use disorder undergoing primary THA have higher rates of: 1) in-hospital lengths of stay (LOS); 2) complications (medical/implant-related); and 3) costs. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Those who misused alcohol were found to be 15 times more likely to develop any acute postoperative infection compared to controls [ 29 ]. These findings are in agreement with those of two recent retrospective studies, one in THA and the other in TKA, both showing significantly higher LOS, increased odds of medical complications (including venous thromboembolism), two-year implant-related complications and healthcare costs [ 30 , 31 ]. Low to moderate alcohol consumption, on the other hand, was associated with lower rates of 90-day and one-year mortality as well as 30-day cardiovascular disease after THA or TKA compared to abstainers [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Those who misused alcohol were found to be 15 times more likely to develop any acute postoperative infection compared to controls [ 29 ]. These findings are in agreement with those of two recent retrospective studies, one in THA and the other in TKA, both showing significantly higher LOS, increased odds of medical complications (including venous thromboembolism), two-year implant-related complications and healthcare costs [ 30 , 31 ]. Low to moderate alcohol consumption, on the other hand, was associated with lower rates of 90-day and one-year mortality as well as 30-day cardiovascular disease after THA or TKA compared to abstainers [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, studies have found that drinking alcohol has little effect on wound infection [ 33 , 34 ]. Alcohol use disorder may, however, play a role, but none of our subjects had this illness [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates the high-risk profile of amphetamine abuse for THA outcomes, which is similar to risks seen in alcohol misuse and tobacco use. In one study of nationwide claims data assessing outcomes following THA, patients with alcohol misuse had longer LOS (4 days vs 3 days, P < .0001) and higher risk of 90-day medical complications (45.94% vs 12.25%; OR, 2.89, P < .0001) and 2-year implant-related complications (17.71% vs 8.46%; OR, 1.97, P < .0001) [ 8 ]. Tobacco use, on the other hand, has been shown to carry a higher risk for infection requiring revision surgery (OR 1.54, 95% CI 1.25-1.91) via meta-analysis [ 9 ], as well as have higher risk for postoperative medical complications and increased mortality [ 10 ].…”
Section: Discussionmentioning
confidence: 99%